2021
DOI: 10.1017/s0142716421000527
|View full text |Cite
|
Sign up to set email alerts
|

The impact of audio on the reading of intralingual versus interlingual subtitles: Evidence from eye movements

Abstract: This study investigated how semantically relevant auditory information might affect the reading of subtitles, and if such effects might be modulated by the concurrent video content. Thirty-four native Chinese speakers with English as their second language watched video with English subtitles in six conditions defined by manipulating the nature of the audio (Chinese/L1 audio vs. English/L2 audio vs. no audio) and the presence versus absence of video content. Global eye-movement analyses showed that participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Negi & Mitra (2020) eye-tracking study of subtitled videos revealed that fixation duration can be a useful metric to trace the learning process. Other eye-tracking studies investigate the impact of audio on the reading of subtitles (Liao et al, 2022) and make recommendations for future cognitive research in the field of audiovisual translation (Kruger et al, 2015).…”
Section: Related Workmentioning
confidence: 99%
“…Negi & Mitra (2020) eye-tracking study of subtitled videos revealed that fixation duration can be a useful metric to trace the learning process. Other eye-tracking studies investigate the impact of audio on the reading of subtitles (Liao et al, 2022) and make recommendations for future cognitive research in the field of audiovisual translation (Kruger et al, 2015).…”
Section: Related Workmentioning
confidence: 99%